Seizure activity and unresponsiveness after hydroxycut ingestion - Kockler, D R; McCarthy, M W; Lawson, C L (Pharmacotherapy, 2001)
A 22-year-old man was hospitalized after unexplained seizure-like activity and unresponsiveness. A urine toxicology screen was negative for salicylates, acetaminophen, alcohol, and drugs of abuse. Medical history was insignificant with the exception of recent (within 2 wks) ingestion of Hydroxycut is a dietary supplement purported to be energy enhancing, muscle building, and fat burning. The agent contains ephedra alkaloids and caffeine, which are both central nervous system stimulants; the etiology of seizure was attributed to their consumption. Due to a significant number of reported adverse events, the United States Food and Drug Administration (FDA) proposed regulations for dietary supplements containing ephedra alkaloids and requested an independent review of case reports linked to these products. Because herbal products are not subject to the same rigorous FDA regulations required for prescription and over-the-counter products, consumers unknowingly risk adverse effects when taking these products. Questioning patients about consumption of herbal products should be part of routine medical visits.